2018
DOI: 10.21776/ub.jpacr.2018.007.02.351
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Activated of Indonesian Bentonite as A Low-Cost Adsorbent for Procion Red Removal from Aqueous Solution

Abstract: Abundant and inexpensive Indonesian natural bentonite was activated by thermal activation at 500 o C for removal of procion red dye as one of the most used synthetic dye in the traditional songket fabric production around Palembang city. Activated bentonite product was characterized by FT-IR, XRD, and thermal analysis. The adsorption process was conducted in batch adsorption system by applying various adsorption parameter condition including, initial pH condition, contact time, and initial dye concentration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Taher et al. (2018) have reported that thermal activation showed a decrease in montmorillonite crystals' intensity at 2θ 5 o in their study [ 21 ]. This phenomenon indicates a dehydration process or a loss of water molecules between the crystal sheet and distortion of the crystalline structure due to the high temperatures used in thermal activation [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taher et al. (2018) have reported that thermal activation showed a decrease in montmorillonite crystals' intensity at 2θ 5 o in their study [ 21 ]. This phenomenon indicates a dehydration process or a loss of water molecules between the crystal sheet and distortion of the crystalline structure due to the high temperatures used in thermal activation [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Modification of bleaching is needed to achieve the desired butter quality of tengkawang butter [ 18 ]. Various ways of modifying the bleaching process activate adsorbents, added chemicals, and heaters [ 18 , 19 , 20 , 21 ]. Using adsorbent is the most commonly used because it is relatively useful and low-cost to bleach vegetable oil.…”
Section: Introductionmentioning
confidence: 99%
“…32, Ogan Ilir, South Sumatra, Indonesia. E-mail: Corresponding author: aldeslesbani@pps.unsri.ac.id Various adsorbents have been used to remove dyes from wastewater such as bentonite [9], kaoline, activated carbon, zeolites, and hydrotalcite [10][11][12]. Hydrotalcite is a class of clay materials and serves as effective sorbents [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic materials can be classi ed by layered materials (Ma et al, 2009) and porous materials (Abdelrahman, 2018). Each of these materials has advantages as adsorbents (Taher et al, 2018;Palapa et al, 2018c), catalyst (Jadhav et al, 2007), ion exchangers (Lins et al, 2018) and sensors (Xu et al, 2018b). One of the most interesting material is layered materials (Mishra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most interesting material is layered materials (Mishra et al, 2018). Based on its existence, nature layered materials such as kaolinite and bentonite (Taher et al, 2018(Taher et al, , 2017 then synthesized layered material such as layered double hydroxides or hydrotalcite (Jadhav et al, 2007;Lesbani et al, 2018;Palapa et al, 2018b). Nowadays, researchers had been interesting to layered materials especially layered double hydroxides.…”
Section: Introductionmentioning
confidence: 99%